Decision Support System for Best Teacher Selection using the Multi-Objective Optimization on the Basic of Ratio Analysis (MOORA) - Sudarsono, Bernadus Gunawan; Karim, Abdul (Journal of Computer System and Informatics (JoSYC), 2024)
Teachers are one of the most important assets owned by companies in their efforts to maintain survival, develop, ability to compete and earn profits. The selection of the best teachers will produce valid and useful information for employee administrative decisions such as promotions, training, transfers including reward systems and other decisions. Decision Support System is a computerized system and is designed to increase the effectiveness in decision making to solve semi-structured and unstructured problems so that the decision making process can be of higher quality. This application that will be made is an application that is guided by the MOORA method. The calculation results using the MOORA method revealed that alternative A5 shows the best performance with a score of 1.246, while alternative A9 occupies the lowest position with a score of 0.546.